Dc and ac electrical response of MOCVD grown GaN in p-i-n structure, assessed through I-V and admittance measurement - Kuruoglu, Neslihan Ayarci; Ozdemir, Orhan; Bozkurt, Kutsal; Sundaram, Suresh; Salvestrini, Jean-Paul; Ougazzaden, Abdallah; Gaimard, Quentin; Belahsene, Sofiane; Merghem, Kamel; Ramdane, Abderrahim (IOP PUBLISHING LTD, 2017)
The electrical response of gallium nitride (GaN), produced through metal-organic chemical vapor deposition in a p-i-n structure was investigated through temperature-dependent current-voltage (I-V) and admittance measurement. The I-V curves showed double diode behavior together with several distinct regions in which trap-assisted tunnelling current has been identified at low and moderate forward/reverse direction and space charge limited current (SCLC) at large forward/reverse bias. The value of extracted energy (similar to 200 meV in forward and similar to 70 meV in reverse direction) marked the tunnelling entity as electron and heavy hole in the present structure. These values were also obtained in space charge limited regime and considered as minority carriers which might originate the experimentally observed negative capacitance issue at low frequencies over the junction under both forward and reverse bias directions. Analytically derived expression for the admittance in the revised versions of SCLC model was also applied to explain the inductance effect, yielding good fits to the experimentally measured admittance data.
Keywords: temperature-dependent current-voltage characteristics; capacitance voltage characteristics; p-i-n diodes; gallium nitride; trap-assisted tunnelling current; LIGHT-EMITTING-DIODES; NEGATIVE CAPACITANCE; JUNCTION DIODES; HOLE MOBILITIES; CHARGE; Physics